2020
DOI: 10.1007/978-981-15-1059-5_3
|View full text |Cite
|
Sign up to set email alerts
|

Designing a Nonlinear Tri Core Photonic Crystal Fiber for Minimizing Dispersion and Analyzing it in Various Sensing Applications

Abstract: Nowadays, optical fiber sensors are playing an important role in bio-sensing applications. Depending on the applications, suitable types of fiber sensors have been produced timely. The aim of these sensors is to provide better sensitivity and high detection capabilities. Thereafter, these tri-core fibers can be applied to sense various substances like salinity, glucose, stress, and temperature. This kind of sensing PCF was introduced by Philip Russell in 1991. In 1996, his group declared the first example of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…It is particularly useful in situations where the dataset is imbalanced, and the classes are not evenly distributed. [21][22][23][24]…”
Section: Machine Learning Algorithms For Pathogen Detectionmentioning
confidence: 99%
“…It is particularly useful in situations where the dataset is imbalanced, and the classes are not evenly distributed. [21][22][23][24]…”
Section: Machine Learning Algorithms For Pathogen Detectionmentioning
confidence: 99%
“…example is reported where they combines finite element simulations and clustering for the identification of photonic modes [14] with large local field energies and specific spatial properties. It is shown that the combination of machine learning with photonics [15] can revolutionize one of the most important fields in optical imaging.…”
Section: Gst467 With Ai (A) Schematic Cross-section Of the Hybrid Waveguide (B)and(c) Fundamental Quasi-transversal Electric (Te) Mode Prmentioning
confidence: 99%
“…The silica glass is easily available and have some characteristics due to this it is preferred for designing PCF structures. Below Table 1 depicts some properties of silica glass [15].…”
Section: Proposed Dual Core Pcf Design Integrated With Aimentioning
confidence: 99%
See 1 more Smart Citation
“…These sensors offer high surface area in low volume and depict extraordinary sensing properties in biomedical and pharma industries. Various meta materials [8] lead to the advancement of photonics in the designing, modeling and simulating PCF structures. PCF sensors along with dedicated FDTD (finite difference time domain) [9] method among available techniques like finite element method (FEM), scalar effective index method (SEIM), full vectorial method (FVM), full vectorial effective index method (FVEIM) etc uses to analyze and produces outcomes.…”
Section: Introductionmentioning
confidence: 99%